Exploration of natural compounds against the human mpox virus DNA-dependent RNA polymerase in silico - Jameel M. Abduljalil; Abdo A. Elfiky; Alaa M. Elgohary (Elsevier, 2023)
Background: Last year, the human monkeypox virus (hMPXV) emerged as an alarming threat to the community, with a detectable outbreak outside the African continent for the first time. According to The American Centers for Disease Control and Prevention (CDC), the virus is reported globally, with 86,746 confirmed cases (until April 08, 2023). DNA-dependent RNA polymerase (DdRp) is an essential protein for viral replication; hence it is a promising drug target for developing antiviral drugs against DNA viruses. Therefore, this study was conducted to search for natural compounds that could provide scaffolds for RNA polymerase inhibitors. Methods: In this study, the DdRp structure of hMPXV was modeled and used to screen the natural compounds database (COCONUT). The virtual screening revealed 15 compounds able to tightly bind to the active site of the DdRp (binding energies less than −7.0 kcal/mol) compared to the physiological nucleotide, guanosine triphosphate (GTP). Molecular dynamics simulation was then performed on the top four hits and compared to GTP Results: The results revealed the potential of four compounds (comp289, comp295, comp441, and comp449) in binding the hMPXV DdRp active site with a comparable binding affinity (−17.06 ± 2.96, −11.6 ± 5.34, −14.85 ± 2.66, and −10.79 ± 4.49 kcal/mol) with GTP (−21.03 ± 7.55 kcal/mol) Conclusion: These findings may also pave the way for developing new hMPXV inhibitors based on natural product scaffolds. These results need further experimental validation but promising as it was validated by unbiased all-atom MD simulations and binding free energy calculations.